Adult Survivors of Childhood Cancer Have Poor Adherence to Dietary Guidelines. Issue 12 (19th October 2016) - Zhang, Fang Fang; Ojha, Rohit P; Krull, Kevin R; Gibson, Todd M; Lu, Lu; Lanctot, Jennifer; Chemaitilly, Wassim; Robison, Leslie L; Hudson, Melissa M
Abstract: Background: Poor nutritional intake can exacerbate the chronic disease burden in childhood cancer survivors, whereas a healthful diet serves a protective function. Few studies have provided detailed evaluations of the diet of childhood cancer survivors. Objectives: This study aimed to evaluate diet quality and dietary intakes of key food groups and nutrients in a large cohort of childhood cancer survivors and whether cancer and treatment characteristics have an impact on survivors' long-term intake. Methods: Diet was assessed in 2570 adult survivors of childhood cancer enrolled in the St. Jude Lifetime cohort (mean age = 32.3 y) by using the Block food-frequency questionnaire. The Healthy Eating Index–2010 (HEI-2010) was calculated to quantify diet quality. Cancer diagnosis and treatment exposure were abstracted from medical records. Differences in HEI-2010 by patient characteristics and treatment exposure were examined by using ANCOVA. Results: The mean ± SD HEI-2010 in childhood cancer survivors was 57.9 ± 12.4 of a maximum score of 100. Referenced to Dietary Reference Intakes, survivors consumed inadequate amounts of vitamin D, vitamin E, potassium, fiber, magnesium, and calcium (27%, 54%, 58%, 59%, 84%, and 90% of the recommended intakes) but excessive amounts of sodium and saturated fat (155% and 115% of the recommended intakes) from foods. Survivors diagnosed when <5 y of age had a lower diet quality than did those diagnosed when ≥5 y of age (mean HEI-2010 score: 56.9 compared with 58.2; P = 0.046). Survivors who received higher radiation doses to the abdomen had a lower diet quality than those who received lower doses (mean HEI-2010 scores = 58.9, 57.2, 56.7, and 56.1 for doses of 0, 1–19.9, 20–29.9, and ≥30 Gy, respectively; P = 0.02). Conclusions: Long-term childhood cancer survivors have poor adherence to the 2010 Dietary Guidelines for Americans. Findings reinforce the need to incorporate nutrition into cancer care to improve diet quality and to reduce morbidities.